Analysis of the Implementation of Administration and Accountability of the Expenditure Treasurer Based on Permendagri Number 77 of 2020 at the Regional Inspectorate of North Sulawesi Province - Saadah, Amelia; Pangerapan, Sonny; Datu, Christian (PT FORMOSA CENDEKIA GLOBAL, 2025)
Good regional financial management requires accurate and transparent administration. With a good governance system, local governments can present accurate financial reports, which is the basis for financial accountability. The expenditure treasurer has an important role in managing regional finances, especially in terms of budget expenditure. The purpose of the study is to find out the process of implementing the administration and accountability of the expenditure treasurer based on the Minister of Home Affairs Regulation Number 77 of 2020. The research method uses a descriptive qualitative method. Data collection method through interviews, observations, and documentation. The results of the study show that the Regional Inspectorate of North Sulawesi Province in the implementation of administration and accountability to the expenditure treasurer is in accordance with Permendagri Number 77 of 2020.